ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA TIPE HOTS MENGGUNAKAN TEORI NEWMAN DI KELAS X SMA NEGERI 1 SIBOLGA - Lubis, Mara Samin; Lubis, Nur Ainun (Math Educa Journal, 2024)
This research aims to analyze the errors made by students in solving HOTS type mathematics problems using the Newman Theory approach in Class X of SMA Negeri 1 Sibolga. The research method used in this study is a qualitative approach which aims to analyze students' errors in solving HOTS type mathematics problems using Newman Theory. Data collection was carried out through tests and interviews. A total of 12 students were selected who became interview subjects, where each student was interrogated regarding their performance in solving the given HOTS questions. Triangulation is used as a technique for checking the validity of the data. The research results show that students' errors in solving HOTS type mathematics problems can be classified into several categories, such as conceptual errors, errors in understanding the questions, and errors in choosing a solution strategy. In addition, factors such as lack of understanding of concepts, confusion in formulating resolution strategies, and time pressure also contribute to the occurrence of these errors.